ANALISIS GAYA BAHASA PADA PUISI “AKU” KARYA CHAIRIL ANWAR - riska desyana; risma despryanti; amalia siddiqa rahayu; yeni Rostikawati (IKIP Siliwangi, 2018)
In making a literature, a writer has his/her or own way in order to make his/her masterpiece has its characters. The reason why the writer took this title is to find out the style which use by one of the famous Indonesian man of style called Chairil Anwar, also the write wants to contribute in growing up Indonesian language especially poem analysis. This research focuses on describing the word style in a poem entitled “Aku” by Chairil Anwar which has many language styles such as comparing language styles, stressed, and repeatation. This research uses descriptive qualitative analys. Data analys has been done by using three steps they are reference studies by reading, noted, and identifying the words which has its style.